Obravnava folklornih obrazcev v osnovnošolskih berilih in revijah - Babič, Saša (Jezik in slovstvo, 2019)
The purpose of the article is to review and present proverbs and riddles as part of folklore in primary school magazines, which are often also a didactic tool in school lessons, as well as in school readers. The analysis focuses on these materials in the children's magazines Zmajček, Ciciban and Cicido, and in the youth magazine Pil in 2015, as well as in primary school readers for the entire period of primary school. Particular attention was devoted to units specifically intended to deal with the genre of proverbs and riddles. At least at the beginning of schooling, children are not (completely) competent in the use of figurative language and metaphorical concepts, and are still in the process of learning this use of language. It was not therefore expected that the level of use of figurative language would be high. Some folklore forms were nonetheless expected, at least as a presentation of the separate genre of proverb and riddle. However, the results of the research showed the opposite: the texts in question are mainly covered by tales, and partly by folklore songs, but even these are poorly represented, while short folklore forms are the worst represented. The findings raise the question of the extent to which the intangible heritage is truly appreciated in Slovenian society, even though it is priceless heritage: folklore forms are an important element and indicator of society, its concepts, aspects and experiences as part of the intangible cultural heritage, language and composition in folklore. At the same time, they enable the use of metaphorical expression and the figurative use of language.
Keywords: berila; osnovne šole; otroške revije; pregovori; slovstvena folklora; uganke